Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure! Let's tackle the problem step by step.
### Part (a): Finding the constants [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]
We start by expanding the polynomial [tex]\((x + 5)(x - 4)(x - a)\)[/tex] and then comparing the resulting polynomial with the given polynomial [tex]\( x^3 + bx^2 - 23x + c \)[/tex].
1. Expand the given polynomial:
[tex]\[ (x + 5)(x - 4)(x - a) \][/tex]
2. First, expand [tex]\((x + 5)(x - 4)\)[/tex]:
[tex]\[ (x + 5)(x - 4) = x^2 - 4x + 5x - 20 = x^2 + x - 20 \][/tex]
3. Next, expand [tex]\((x^2 + x - 20)(x - a)\)[/tex]:
[tex]\[ (x^2 + x - 20)(x - a) = x^3 - ax^2 + x^2 - 20x + a x - 20a \][/tex]
4. Combine like terms:
[tex]\[ x^3 + (1 - a)x^2 + (a - 20)x - 20a \][/tex]
5. Compare this with [tex]\(x^3 + bx^2 - 23x + c\)[/tex]:
From the comparison:
[tex]\[ x^3 + (1 - a)x^2 + (a - 20)x - 20a = x^3 + bx^2 - 23x + c \][/tex]
Equating coefficients, we get:
[tex]\[ 1 - a = b \][/tex]
[tex]\[ a - 20 = -23 \][/tex]
[tex]\[ -20a = c \][/tex]
6. Solve for [tex]\(a\)[/tex]:
[tex]\[ a - 20 = -23 \implies a = -3 \][/tex]
7. Solve for [tex]\(b\)[/tex]:
[tex]\[ 1 - a = b \implies 1 - (-3) = b \implies b = 4 \][/tex]
8. Solve for [tex]\(c\)[/tex]:
[tex]\[ -20a = c \implies -20(-3) = c \implies c = 60 \][/tex]
So, the values of the constants are:
[tex]\[ a = -3, \quad b = 4, \quad c = 60 \][/tex]
### Part (b): Solving the inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex]
To solve the inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex], we need to determine the roots of the cubic polynomial.
1. Find the roots:
Use the polynomial [tex]\(x^3 + 4x^2 - 23x + 60\)[/tex]. We will use factor theorem or other root-finding methods.
Using trial and error or other factorization methods, we find that the roots are:
[tex]\[ x = -5, \quad x = 3, \quad x = 4 \][/tex]
2. Factor the polynomial:
[tex]\[ x^3 + 4x^2 - 23x + 60 = (x + 5)(x - 3)(x - 4) \][/tex]
3. Determine where the factors change sign to solve the inequality [tex]\( (x + 5)(x - 3)(x - 4) < 0 \)[/tex]:
- Roots are [tex]\( x = -5, x = 3, x = 4 \)[/tex].
- Test intervals between the roots:
- For [tex]\( x < -5 \)[/tex]: All factors are negative or positive leading to [tex]\( > 0 \)[/tex].
- For [tex]\( -5 < x < 3 \)[/tex]: One factor is negative, meaning the product [tex]\( < 0 \)[/tex].
- For [tex]\( 3 < x < 4 \)[/tex]: Two factors are negative, resulting in product [tex]\( > 0 \)[/tex].
- For [tex]\( x > 4 \)[/tex]: All factors are positive, leading to [tex]\( > 0 \)[/tex].
4. Combine the intervals:
Therefore, the solution for the inequality is:
[tex]\[ -5 < x < 3 \][/tex]
### Summary:
- The values of the constants are:
[tex]\[ a = -3, \quad b = 4, \quad c = 60 \][/tex]
- The inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex] is satisfied when:
[tex]\[ -5 < x < 3 \][/tex]
### Part (a): Finding the constants [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]
We start by expanding the polynomial [tex]\((x + 5)(x - 4)(x - a)\)[/tex] and then comparing the resulting polynomial with the given polynomial [tex]\( x^3 + bx^2 - 23x + c \)[/tex].
1. Expand the given polynomial:
[tex]\[ (x + 5)(x - 4)(x - a) \][/tex]
2. First, expand [tex]\((x + 5)(x - 4)\)[/tex]:
[tex]\[ (x + 5)(x - 4) = x^2 - 4x + 5x - 20 = x^2 + x - 20 \][/tex]
3. Next, expand [tex]\((x^2 + x - 20)(x - a)\)[/tex]:
[tex]\[ (x^2 + x - 20)(x - a) = x^3 - ax^2 + x^2 - 20x + a x - 20a \][/tex]
4. Combine like terms:
[tex]\[ x^3 + (1 - a)x^2 + (a - 20)x - 20a \][/tex]
5. Compare this with [tex]\(x^3 + bx^2 - 23x + c\)[/tex]:
From the comparison:
[tex]\[ x^3 + (1 - a)x^2 + (a - 20)x - 20a = x^3 + bx^2 - 23x + c \][/tex]
Equating coefficients, we get:
[tex]\[ 1 - a = b \][/tex]
[tex]\[ a - 20 = -23 \][/tex]
[tex]\[ -20a = c \][/tex]
6. Solve for [tex]\(a\)[/tex]:
[tex]\[ a - 20 = -23 \implies a = -3 \][/tex]
7. Solve for [tex]\(b\)[/tex]:
[tex]\[ 1 - a = b \implies 1 - (-3) = b \implies b = 4 \][/tex]
8. Solve for [tex]\(c\)[/tex]:
[tex]\[ -20a = c \implies -20(-3) = c \implies c = 60 \][/tex]
So, the values of the constants are:
[tex]\[ a = -3, \quad b = 4, \quad c = 60 \][/tex]
### Part (b): Solving the inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex]
To solve the inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex], we need to determine the roots of the cubic polynomial.
1. Find the roots:
Use the polynomial [tex]\(x^3 + 4x^2 - 23x + 60\)[/tex]. We will use factor theorem or other root-finding methods.
Using trial and error or other factorization methods, we find that the roots are:
[tex]\[ x = -5, \quad x = 3, \quad x = 4 \][/tex]
2. Factor the polynomial:
[tex]\[ x^3 + 4x^2 - 23x + 60 = (x + 5)(x - 3)(x - 4) \][/tex]
3. Determine where the factors change sign to solve the inequality [tex]\( (x + 5)(x - 3)(x - 4) < 0 \)[/tex]:
- Roots are [tex]\( x = -5, x = 3, x = 4 \)[/tex].
- Test intervals between the roots:
- For [tex]\( x < -5 \)[/tex]: All factors are negative or positive leading to [tex]\( > 0 \)[/tex].
- For [tex]\( -5 < x < 3 \)[/tex]: One factor is negative, meaning the product [tex]\( < 0 \)[/tex].
- For [tex]\( 3 < x < 4 \)[/tex]: Two factors are negative, resulting in product [tex]\( > 0 \)[/tex].
- For [tex]\( x > 4 \)[/tex]: All factors are positive, leading to [tex]\( > 0 \)[/tex].
4. Combine the intervals:
Therefore, the solution for the inequality is:
[tex]\[ -5 < x < 3 \][/tex]
### Summary:
- The values of the constants are:
[tex]\[ a = -3, \quad b = 4, \quad c = 60 \][/tex]
- The inequality [tex]\( x^3 + 4x^2 - 23x + 60 < 0 \)[/tex] is satisfied when:
[tex]\[ -5 < x < 3 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.